Desa Mandiri Gerakan Masyarakat Sehat Untuk Pengendalian Penyakit Tidak Menular Di Lubuk Ruso Kecamatan Pemayung Batang Hari Jambi - Ervon Veriza; Junita; Solihin Sayuti; Iksaruddin; Egy Sunanda Putra (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2022)
Clean and healthy living, including correct diet, regular physical activity, and check-ups. Strengthening the role of the community to be more responsible for their own health status and central and regional government facilities in raising awareness and developing the ability of community-based health efforts is very important and must carried out continuously. Almost 90% of diseases categorized as non-communicable diseases (PTM) such as cancer, diabetes, HIV-AIDS, heart disease, high blood pressure, stress and so on can actually be prevented with regular health behaviors. The purpose of community service is to increase the independence and welfare of the people of Lubuk Ruso Village, Pemayung Batang Hari District, Jambi by empowering the community through the healthy community movement (germas independent village). Activities carried out with the pre test stage, the implementation stage and the evaluation stage with the post test. PkM activities with the acquisition of pre-test scores with a mean value of the comparison between the pre-test post-test is 2.85. Bivariate analysis test results with the Wilcoxon Test on respondents. The results of testing the data show a value of p = 0.000 <0.05, so it can be concluded statistically that there are differences in knowledge before and after education.Keywords: Education, Germas, PTM